Contemporary debates on terrorism - Jackson, Richard; Pisoiu, Daniela (Routledge, Taylor & Francis Group, 2018)
Contemporary Debates on Terrorism is an innovative textbook, addressing a number of key issues in terrorism studies from both traditional and 'critical' perspectives. In recent years, the terrorism studies field has grown in quantity and quality, with a growing number of scholars rooted in various professional disciplines beginning to debate the complex dynamics underlying this category of violence. This second edition has been revised and updated to cover contemporary issues such as the rise of ISIL and cyberterrorism. This book will be essential reading for students of terrorism studies and political violence, critical terrorism studies, security studies and IR in general.